2019
DOI: 10.3390/md17020095
|View full text |Cite
|
Sign up to set email alerts
|

Diphlorethohydroxycarmalol Attenuates Fine Particulate Matter-Induced Subcellular Skin Dysfunction

Abstract: The skin, the largest organ in humans, is exposed to major sources of outdoor air pollution, such as fine particulate matter with a diameter ≤ 2.5 µm (PM2.5). Diphlorethohydroxycarmalol (DPHC), a marine-based compound, possesses multiple activities including antioxidant effects. In the present study, we evaluated the protective effect of DPHC on PM2.5-induced skin cell damage and elucidated the underlying mechanisms in vitro and in vivo. The results showed that DPHC blocked PM2.5-induced reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 40 publications
0
55
0
Order By: Relevance
“…The activated NF-κB subunits (p50 and p65) translated into the nucleus could induce the expression of pro-inflammatory cytokines and MMPs [34,41]. AP-1 could promote several MMPs expression, and it was activated by the phosphorylated MAPKs, which activate by ROS overproduction [34,37]. Thus, in the present study, the activated NF-κB, AP-1, and MAPKs were measured by Western blot assay.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The activated NF-κB subunits (p50 and p65) translated into the nucleus could induce the expression of pro-inflammatory cytokines and MMPs [34,41]. AP-1 could promote several MMPs expression, and it was activated by the phosphorylated MAPKs, which activate by ROS overproduction [34,37]. Thus, in the present study, the activated NF-κB, AP-1, and MAPKs were measured by Western blot assay.…”
Section: Discussionmentioning
confidence: 81%
“…Diphlorethohydroxycarmalol (DPHC, Figure 1), a phenolic compound derived from I. okamurae, which possesses the potential for skin protection [34][35][36]. Previous studies suggested that DPHC could effectively protect skins against epidermic damages induced by UVB irradiation and PM in human keratinocytes (HaCaT cells) [36,37]. In addition, the protective effect of DPHC on UVB-induced dermic damages in human dermal fibroblasts (HDF cells) has been investigated [34].…”
Section: Introductionmentioning
confidence: 99%
“…[46]. Diphlorethohydroxycarmalol 3 decreased the oxidative stress caused to the skin tissue of HR-1 hairless mice by fine particulate matter with a diameter ≤2.5 µm (PM 2.5 ), a major pollutant present in the atmosphere [44] (Table 1). Exposure to PM 2.5 caused lipid peroxidation and protein carbonylation, and increased epidermal height, which were inhibited by 3.…”
Section: Diphlorethohydroxycarmalolmentioning
confidence: 99%
“…Exposure to PM 2.5 caused lipid peroxidation and protein carbonylation, and increased epidermal height, which were inhibited by 3. Moreover, PM 2.5 induced apoptosis and mitogen-activated protein kinase (MAPK) protein expression; however, these changes were attenuated by 3 [44].…”
Section: Diphlorethohydroxycarmalolmentioning
confidence: 99%
See 1 more Smart Citation